Uncommon Septic Arthritis of the Hip Joint in an Immunocompetent Adult Patient Due to Bacillus pumilus and Paenibacillus barengoltzii Managed with Long-Term Treatment with Linezolid: A Case Report and Short Literature Review - Razvan Silviu Cismasiu; Rares-Mircea Birlutiu; Liliana Lucia Preoțescu (MDPI AG, 2023)
The Bacillus and Paenibacillus genera are diverse soil-related bacterial pathogens. In this case report, we describe, to our knowledge, the first report of septic arthritis in a native hip joint in an immunocompetent adult patient caused by Bacillus pumilus and Paenibacillus barengoltzii. We describe the case of a 39-year-old Caucasian male patient who sought medical advice for chronic pain on the mobilization of the right hip, decreased range of motion, and physical asthenia. The patient underwent a surgical intervention (core decompression) for a right osteonecrosis of the femoral head, with a slightly favorable postoperative evolution after surgery for one month. Surgical treatment was planned on the basis of clinical and paraclinical investigations and the joint damage. The hip was explored using an anterior approach under spinal anesthesia and standard antibiotic prophylaxis. After resection of the femoral head, meticulous debridement of all inflammatory tissues was performed, and a preformed temporary spacer was inserted into the femoral canal. Bacteriological laboratory studies identified Bacillus pumilus and Paenibacillus barengoltzii via matrix-assisted laser desorption-ionization time-of-flight mass spectrometry analysis. The patient initially received nine days of empirical therapy with intravenous antibiotics (linezolid and meropenem). After the bacterial strains were identified, the patient received organism-specific antibiotic therapy with the same antibiotics and dose for eight days until discharge. After discharge, the patient was referred to another hospital, where he continued treatment with linezolid for seven weeks and, after that, four weeks of oral therapy with cotrimoxazole and rifampicin. During this period, no severe or potentially life-threatening adverse events were recorded during long-term treatment with linezolid or with the two oral antibiotics. In conclusion, our findings suggest that long-term treatment with linezolid may be a viable option for the management of bone and joint infections caused by Bacillus pumilus and Paenibacillus barengoltzii.